2012
DOI: 10.1007/s10864-011-9144-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Helping Early Literacy with Practice Strategies (HELPS) Reading Fluency Program with Latino English Language Learners: A Preliminary Evaluation

Abstract: The Helping Early Literacy with Practice Strategies (HELPS) Program was developed by integrating 8 evidence-based fluency-building instructional strategies into a structured program that can be feasibly implemented by educators. The HELPS Program has been shown in previous research to significantly improve elementary-aged students' reading abilities, but the effects of HELPS have not been evaluated with an important and increasing sub-population of U.S. students, English language learners (ELLs). As such, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 31 publications
(52 citation statements)
references
References 22 publications
2
48
1
Order By: Relevance
“…Although our findings are only preliminary and should be interpreted with respect to this study's limitations (e.g., a relatively small sample size, only one dependent measure used), it is encouraging to find that these brief interventions resulted in immediate and retention effects that are commensurate with those found in studies that included large sample sizes and numerous measures of reading skills, including comprehension. For example, Begeny and his colleagues (e.g., Begeny 2011;Begeny et al 2010;Begeny and Martens 2006) have shown that Englishspeaking students receiving the fluency-based intervention strategies used in the present study made immediate and/or retention gains similar to the students in this study and made statistically significant gains in broad measures of reading, including comprehension. Of course, future research using broader measures and in varied locations to evaluate the interventions developed for the present study are warranted, but the present study (combined with similar research in this area; e.g., Therrien 2004) offers meaningful support for the brief, SG and 1:1 interventions implemented with our Spanish-speaking students.…”
Section: Implications and Limitationssupporting
confidence: 55%
See 1 more Smart Citation
“…Although our findings are only preliminary and should be interpreted with respect to this study's limitations (e.g., a relatively small sample size, only one dependent measure used), it is encouraging to find that these brief interventions resulted in immediate and retention effects that are commensurate with those found in studies that included large sample sizes and numerous measures of reading skills, including comprehension. For example, Begeny and his colleagues (e.g., Begeny 2011;Begeny et al 2010;Begeny and Martens 2006) have shown that Englishspeaking students receiving the fluency-based intervention strategies used in the present study made immediate and/or retention gains similar to the students in this study and made statistically significant gains in broad measures of reading, including comprehension. Of course, future research using broader measures and in varied locations to evaluate the interventions developed for the present study are warranted, but the present study (combined with similar research in this area; e.g., Therrien 2004) offers meaningful support for the brief, SG and 1:1 interventions implemented with our Spanish-speaking students.…”
Section: Implications and Limitationssupporting
confidence: 55%
“…In many of these studies, fluency-based strategies have enhanced other important reading abilities, including comprehension (e.g., Begeny 2011;NICHHD 2000). Effective strategies for improving students' reading fluency include repeated reading (e.g., Therrien 2004), modeling (e.g., Skinner et al 1997), phrase-drill error-correction (e.g., , and motivational/reward procedures (e.g., Haring et al 1978).…”
Section: Reading Fluency Researchmentioning
confidence: 99%
“…This program requires 1-to-1 instruction with a trained adult and is implemented outside of the classroom. ELs receiving HELPS showed significant benefits in reading fluency and comprehension compared to ELs not receiving the intervention (Begeny et al 2012).…”
Section: Introductionmentioning
confidence: 89%
“…In many instances, the types of instruction demonstrated to be most effective for at-risk students, in particular ELs, often require 1-to-1 tutorial sessions and/or must be conducted outside of the regular classroom environment (e.g., Begeny et al 2012;Vadasy and Sanders 2011). A blended learning approach when properly implemented may provide a viable alternative to these types of instruction.…”
Section: Benefits Of Blended Learningmentioning
confidence: 99%
See 1 more Smart Citation